The combined effects of land‐use legacies and novel fire regimes on bird distributions in the Mediterranean. (17th April 2013) - De Cáceres, Miquel; Brotons, Lluís; Aquilué, Núria; Fortin, Marie‐Josée
Abstract: Aim: We investigate first whether fire regimes resulting from the combination of climate change and fire‐fighting policy may affect species distributions in Mediterranean landscapes, and second to what extent distributional dynamics may be constrained by the spatial legacy of historical land use. Location: Catalonia (north‐eastern Spain). Methods: We modelled the distributional responses of 64 forest and open‐habitat bird species to nine fire‐regime scenarios, defined by combining different levels of climate change and fire suppression efficiency. A fire‐succession model was used to stochastically simulate land‐cover changes between 2000 and 2050 under these scenarios. We used species distribution models to predict habitat suitability and occupancy dynamics under either no dispersal or full dispersal assumptions. Results: Under many simulated scenarios, the succession from shrubland to forest dominated over the creation of new low‐vegetation areas derived from wildfires. Consequently, open‐habitat specialists were the group most affected by losses of suitable habitat. Fire regimes obtained under scenarios including high fire suppression efficiency resulted in a larger number of bird species experiencing reductions in their distribution area. Main conclusions: Anthropogenic factors, such as historical land‐use change and fire suppression, can drive regional distribution dynamics in directions opposite to those expected from climatic trends. This raises the question of what drivers and interactions should be given priority in the prediction of biodiversity responses to global change at the regional scale.